Tinjauan Potensi Agrowisata Di Kawasan Bedugul - Manatar Situmorang; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2017)
The research describes the identification of the potential of tourism in the region Bedugul. One of the atraction in this area is on Agrotourism. That potential includes the rural atmosphere, and horticulture plantation, and forestry. Furthermore, this study will describe the activities of agrotourism, the stakeholders, and the use of agro-tourism in the region Bedugul. The agro-tourism benefits are divided into three elements, namely the environmental benefits, economic benefits, and socio-culturalbenefits. This research is a qualitative character. Nevertheless, this study also uses quantitative data as a complement. Data collection techniqueis done through observation, interviews, and literature. Informants determined through purposive sampling. For the analyzed data, the technique used is descriptive qualitative. The results show that the potential of agro-tourism in the region Bedugul include strawberry plantations and vegetables, Lake Buyan, and Botanical Gardens Bedugul. Meanwhile, agro-tourism activities in the region by the local people who get a carrying capacity of Government (planning and spatial) and private sector (accommodation and restaurants). Communities also get economic benefits (income and be an entrepeneur), environment (land optimization and conservation) and socio-cultural benefits. Keywords: Agro, Government, Private Sector, Local Communities, Bedugul Area